Thesis Review: State Capacities and Sectoral Policies in Science, Technology, and Innovation. An Analysis of the Trajectory of the Argentine Sectoral Fund (Argentina, 2010-2023). (Desarrollo, Estado y Espacio, 2025)
This thesis analyzes the sectoral science, technology, and innovation (STI) policies and instruments promoted through the Argentine Sectoral Fund (FONARSEC) between 2010 and 2023. It adopts a dynamic and relational approach to the state capacities involved in their design and implementation, understood as configurations that are updated in the interaction between state resources (bureaucratic, economic-financial, and organizational) and historical trajectories, political orientations, internal dynamics, and links with social and productive actors.
Keywords: Mercosur; industry policies